2011
DOI: 10.3174/ajnr.a2590
|View full text |Cite
|
Sign up to set email alerts
|

Mesial Prefrontal Cortex Degeneration in Amyotrophic Lateral Sclerosis: A High-Field Proton MR Spectroscopy Study

Abstract: BACKGROUND AND PURPOSE:Frontotemporal lobar degeneration is responsible for the cognitive abnormalities seen in patients with ALS. We sought to evaluate the in vivo neurochemical changes associated with this pathology indicative of neuronal loss and gliosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…41 Another study found trends for reductions in NAA and elevations of myo-inositol levels in the mesial prefrontal cortex. 110 Overall, the NAA:myo-inositol ratio was significantly decreased in patients with ALS, but did not correlate with verbal fluency or cognitive performance. Another study reported decreases in the NAA:Cr ratio in the frontal lobe, and these changes correlated with achievement on the Wisconsin Card Sorting Test.…”
Section: Advanced Neuroimaging In Alsmentioning
confidence: 83%
“…41 Another study found trends for reductions in NAA and elevations of myo-inositol levels in the mesial prefrontal cortex. 110 Overall, the NAA:myo-inositol ratio was significantly decreased in patients with ALS, but did not correlate with verbal fluency or cognitive performance. Another study reported decreases in the NAA:Cr ratio in the frontal lobe, and these changes correlated with achievement on the Wisconsin Card Sorting Test.…”
Section: Advanced Neuroimaging In Alsmentioning
confidence: 83%
“…The presence of frontotemporal lobar degeneration (FTLD) is supported by reduced NAA indices in various frontal regions including the dorsolateral (11, 23) and mesial prefrontal (19, 45) cortices. Mesial prefrontal cortex neurochemistry is abnormal in patients who for the most part are not cognitively impaired, suggesting MRS may be more sensitive to detecting FTLD than clinical measures (45). “Extra-motor” degeneration was similarly demonstrated in the mid-cingulate gyrus (34), thalamus (34, 46), and basal ganglia (46).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the visual cortex has been shown through histologic and MR measures to remain unaffected during the disease process and comparable to normal age‐matched control tissue . While the aPFC was also selected as an internal control initially, there is MR spectroscopic and morphometric evidence to support the involvement of the frontal lobe region in the disease process . In addition, as the control tissue samples were obtained in a previously formalin fixed state, MR images were not able to be obtained from the control tissue to compare with the MR metrics from the fresh nonfixed ALS tissue.…”
Section: Discussionmentioning
confidence: 99%